Silver-graphene oxide nanocomposite film-based SPR sensor for detection of Pb2+ ions - Mukhtar W.M.; Halim R.M.; Dasuki K.A.; Rashid A.R.A.; Taib N.A.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS